Discipleship System among the Prophets of the Old Covenant to the Apostle Paul of the New Covenant - Siregar, Helda Yanti (Scriptura Indonesia, 2025)
This study aims to trace and analyse the development of the discipleship system in the biblical narrative, starting from the prophetic tradition in the Old Testament to the formation of the early churches under the leadership of the apostles and the apostle Paul in the New Testament. Discipleship is understood as an intentional process of spiritual, theological, and ethical formation within the framework of the relationship between a spiritual mentor and his or her successor. In the Old Testament, discipleship is prophetic and symbolic, seen in the Moses-Joshua, Elijah-Elisha, Samuel and his band of disciples, and Isaiah and his band of followers, as well as the community of prophets that emerged in the historical context of Israel. This system emphasised the inheritance of charisma, prophetic authority, and the internalisation of God's law. Entering the New Testament, Jesus introduced an incarnational and relational discipleship paradigm, emphasising the transformation of the totality of life through direct engagement in the life of the Master. The Apostle Paul then institutionalised this discipleship practice in the context of the early Christian community, with structured patterns of teaching, multiplicative discipleship, and a focus on the reproduction of spiritual leaders. This paper utilises a theological-demonological and historical-critical approach to identify both continuities and conceptual transitions in the practice of discipleship, and offers implicative reflections for the development of a contemporary discipleship system that is contextualised and rooted in the biblical heritage.